A Comparison of Reinforcement Planning for Basement Wall Shelter Based on SS EN 1990: 2008 (2015) with Technical Requirements for Household Shelter 2023 - Fenia Hayatun Nikmah; Usmanul Hayadi Umar (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2023)
Singapore is an example that applies the concept of household housing, namely buildings that are used as evacuation places. One of the buildings that applies the household residential concept is a detached type of residential house with a basement located at 102 Jalan Langgar Bedok, Bedok Planning Area, Singapore in an HDB housing block. The technical guidebook used as a guideline for building household shelters is